THE EFFECT OF TAI-CHI EXERCISE ON ADEQUACY OF HEMODIALYSIS AMONG PATIENTS WITH END STAGE RENAL DISEASE: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i2.98 - Andi Sudrajat; Krisna Yetti; Agung Waluyo (Alta Dharma Publisher, 2019)
Abstract End stage renal disease (ESRD) is currently a global problem because of its increasing prevalence. Hemodialysis is the main management in ESRD patients. The importance of assessing the adequacy of dialysis greatly influences the quality and continuity of the patient's life. This paper is a literature review to identify the effect of i tai chi exercise on the adequacy of hemodialysis in ESRD patients. The authors used several databases to search for literary sources to be studied, namely Web of Science, EBSCO, PubMed, and Google Scholar. It was found that tai chi is a safe therapy less complications and have beneficial for ESRD patients. Tai chi can suppress bone reabsorption, improve functional balance and strength, increase the rate of blood in the muscles, increase capillary size and surface area which results in increased movement of toxins and urea in cells that move to the vascular eventually towards the hemodialysis machine. In addition, tai chi can be beneficial to make circulation smooth, reduce blood pressure, and facilitate the release of lactic acid so that it can reduce risk factors for cardiovascular disease. Tai chi is recommended as a treatment modality choice to increase the adequacy of hemodialysis in ESRD patients. Keywords: adequate dialysis, ESRD, hemodialysis, intradialysis exercise, tai chi.